1989
DOI: 10.1142/s0217984989000443
|View full text |Cite
|
Sign up to set email alerts
|

A Raman Spectroscopic Study of Barium Copper Oxide

Abstract: Various physical treatments of BaCuO 2 samples result in irreversible changes in its Raman spectrum. The prominent peaks at 576 and 628 cm −1 in the spectra of sintered pellets of BaCuO 2 disappear upon further annealing in air or oxygen or upon mere regrinding of the pellets. Further annealing in air, oxygen, or vacuum does not restore these peaks. Similar but less intense peaks reappear upon exposure of pellets to laboratory environment for several weeks, but these broaden and disappear upon further exposure… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

1990
1990
2013
2013

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 0 publications
0
4
0
Order By: Relevance
“…The effects of TU-silver complexes on tin nucleation and growth kinetics can be explained by an induced adsorption and ion-bridging mechanism. 50,51 TU is adsorbed on copper [52][53][54][55][56][57] and silver electrodes. 53,[58][59][60][61] Therefore, the TU-silver complexes are more readily adsorbed on copper and silver substrates than uncomplexed tin ions.…”
Section: Resultsmentioning
confidence: 99%
“…The effects of TU-silver complexes on tin nucleation and growth kinetics can be explained by an induced adsorption and ion-bridging mechanism. 50,51 TU is adsorbed on copper [52][53][54][55][56][57] and silver electrodes. 53,[58][59][60][61] Therefore, the TU-silver complexes are more readily adsorbed on copper and silver substrates than uncomplexed tin ions.…”
Section: Resultsmentioning
confidence: 99%
“…There are three possibilities for ac voltage to improve the quality of the mixed film. First, the chloride ion and H 2 O in NaCl solution may be involved in complexation with PT and copper, 20,21 filling some pinholes or defects in the mixed self-assembled film. Second, several authors reported that there is a small amount of metal dissolutions during the selfassembled process; 22,23 therefore, some Cu cations must retain in the mixed film.…”
Section: Resultsmentioning
confidence: 99%
“…TU can slowly reduce Cu 2+ and form complexes, Cu ͑TU͒ n + ͑n = 1-4͒, with the product; 23 the bonding of TU to the surface copper atoms is assumed to involve Cu-S bond formation. 24 The charge transfer resistance plot for copper deposition in the presence of TU shows a maximum, Fig. 10b, at ca.…”
Section: Sc • Nhmentioning
confidence: 97%